Implementation of Integrated Learning Based Integrated Islamic School Network Curriculum in SMA ABBS Surakarta - Muhammad Munadi; Fitri Ana Ika Dewi (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This research aims to identify the implementation of integrated learning method based on Integrated Islamic School Network curriculum in SMA ABBS of Surakarta. This research is aimed to analyze the integrated phases used in SMA ABBS. Descriptive qualitative research was applied where the data taken from document, events, and informants. The results of the research show that there are three phases of integrated learning: material comprehension, integrated understanding, and practicing the integrated learning. The implementation of integrated learning method in SMA ABBS develops intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). The implementation of integrated learning method based on Integrated Islamic School Network curriculum has ideological foundation sourced from the holy Qur’an and As-Hadits. The successful implementation of this method is due to good cooperation between the committees involved.